Wkład Polaków w rozwój misji mariannhillskiej na przełomie XIX i XX wieku w południowej Afryce - Puchała, Kinga (Annales Missiologici Posnanienses, 2012)
In 1879 Francis Pfanner settled together with 30 co-brothers on the west coast of Southern Africa on Maria-Anna’s Hill (Marianhill). They built the monastery which in the short time became the centre of the Christianity in the entire area Craftsmen workshops and schools started to come into existence. Altogether 265 monks lived in the monastery, many of them from Poland. They started to open new missionary posts, sometimes even up to 200 km away from Marianhill. In 1909 Pope Pius the 10th created a new missionary congregation – Marianhill Missionaries. Their work is still practically unknown. To the large extend it was co-founded by Poles and often supported by them.